2016
DOI: 10.3402/gha.v9.29866
|View full text |Cite
|
Sign up to set email alerts
|

The path to impact of operational research on tuberculosis control policies and practices in Indonesia

Abstract: BackgroundOperational research is currently one of the pillars of the global strategy to control tuberculosis. Indonesia initiated capacity building for operational research on tuberculosis over the last decade. Although publication of the research in peer-reviewed journals is an important indicator for measuring the success of this endeavor, the influence of operational research on policy and practices is considered even more important. However, little is known about the process by which operational research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 14 publications
0
14
0
6
Order By: Relevance
“…Moreover, our previous research revealed that communication problems existed within OR teams [9]. One strength of this study was the in-depth nature of the exploration of the benefits of the OR capacity-building program.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, our previous research revealed that communication problems existed within OR teams [9]. One strength of this study was the in-depth nature of the exploration of the benefits of the OR capacity-building program.…”
Section: Discussionmentioning
confidence: 99%
“…The study informants perceived good examples about research that improved the public health program and influence the policy. Our previous publication explained the impact of this capacity-building program on TB program and policy [9]. In addition, practitioners learned to use evidence to improve TB programs and policy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations